Effect of the concentration of 2,4-dichlorophenoxyacetic acid (2,4-D) in the cauline buds rooting of “raspberry” outbreaks in greenhouse conditions - Mejía Coico, Freddy (2015)
It was determined the effect of 2,4-dichlorophenoxyacetic acid ( 2,4- D ) in the rooting of cauline buds of Rubus idaeus L. in greenhouse conditions as a possible alternative in efficient and reproducible propagation of this crop.Was evaluated the effect of concentrations of 2,4 – D, used in the treatments T0: 0.0% , T1: 0.3 %, T2: 0.5% and T3: 0.8 %. The obtained data were statistically analyzed by the simple variance analysis (ANOVA); and Tukey test. At 30 days it was found that the T1induced the formation of a greater number of roots 6.17cm, greater root length of 13.09 cm and a height of plant 9.13 cm. It is concluded that 2,4-dichlorophenoxyacetic concentrationof0.3% exerted the best effect for rooting from cauline buds of Rubus idaeus L.